Comparative Evaluation of the Microleakage of Self-etch Adhesives on the Pulp Chamber Dentin after Proanthocyanidin Application: An In vitro Study - Vanitha Umesh Shenoy; Yashaswi Rajendra Chaudhari; Anuradha Patil; Sumanthini Venkatsubramanyam Margasahayam; Divya Naik; Jayeeta Verma (Journal of International Clinical Dental Research Organization, 2024)
Background: The long-term success of adhesive restorations is contingent on minimizing microleakage, which can lead to postoperative sensitivity and secondary caries. Sodium hypochlorite (NaOCl) and ethylenediaminetetraacetic acid (EDTA) irrigation are commonly employed during adhesive restorative procedures, but their impact on microleakage remains a concern. Proanthocyanidin (PA), a naturally derived agent, has shown potential in enhancing bond strength. Aim: This study aimed to compare and evaluate the effect of treatment with or without 30% PA of the pulp chamber dentin after 1% NaOCl and 17% EDTA irrigation on the microleakage of adhesive restorations. Materials and Methods: Forty caries-free, freshly extracted permanent human molars were used. The pulp chamber roof was removed, and the roots were resected. Canal orifices were enlarged and sealed. Specimens were divided into four groups based on adhesives (OptiBond All-In-One and Adper Easy One) and irrigation regimens. After irrigation, pulp chambers were restored with Filtek Bulk-Fill composite resin. Microleakage was assessed using methylene blue dye penetration. Results: Microleakage was observed in all groups, irrespective of irrigation protocol and adhesives. PA application showed reduced dye penetration compared to without PA, although not statistically significant. Statistical analysis was performed using Kruskal–Wallis and Mann–Whitney tests at P < 0.05. Conclusion: Irrigation protocols and the use of PA had no significant effect on the microleakage of self-etch adhesives to pulp chamber dentin. A 1-min application of 30% PA solution after NaOCl and EDTA irrigation did not improve the bonding of self-etch adhesives to pulp chamber dentin.